Mathematics Communication Based on Students’ Self – Efficacy in Problem Based Learning Assisted By Mobile Learning - Ashim, Muhammad; Asikin, Mohammad; Kharisudin, Iqbal (Unnes Journal of Mathematics Education Research, 2020)
This research aims to describe mathematics communication skill based on self-efficacy of students in problem based learning assisted by mobile learning. This research was a concurrent embedded. The population was X grade students of MAN 1 Kota Pekalongan. The technique of sampling was purposive sampling. It was selected X MIA 2 as experimental group. The subjects were grouped based on self-efficacy with high, moderate, and low categories to be interviewed about their mathematics communication skill. The instruments were test and interview. The findings showed that PBL assisted by mobile leanring was qualified. The result of mathematics communication description based on self-efficacy was varied, it was shown from 8 students with high self-efficacy, there were 5 students categorized high, 2 categorized moderate, and 1 categorized low. From 20 students with moderate self-efficacy, there were 5 students categorized high, 11 categorized moderate, and 4 categorized low. From 8 students with low self-efficacy, there was only 1 students categorized high, 2 categorized moderate, and 5 categorized low.